Demographic Factors Associated with Presenting for Eye Evaluation in the Partnership for Research on Vaccines and Infectious Diseases in Liberia III Natural History Study of Ebola Virus Disease - Wallace, Augustine C. D.; Ross, Robin D.; Tawse, Kirstin; Nyain, Ruth; Gargu, Catherine; Wentworth, Deborah E.; Bishop, Rachel J.; Eghrari, Allen O. (Middle East African journal of ophthalmology, 2023)
PURPOSE: Survivors of Ebola virus disease (EVD) are at risk for ocular complications after infection. We sought to identify demographic factors associated with the likelihood to present for eye examination among Ebola survivors enrolled in a longitudinal natural history study of EVD. METHODS: The Partnership for Research on Vaccines and Infectious Diseases in Liberia (PREVAIL) III Ebola natural history study is a 5-year study that seeks to identify long-term sequelae of EVD, including ocular sequelae. All survivors enrolled in the PREVAIL parent study from June 2015 to March 2016 were asked to return for comprehensive eye examination through June 2016. Logistic regression was conducted using self-reported survivor status, age, gender, and distance from the hospital as covariates. RESULTS: A total of 1448 subjects enrolled in the parent PREVAIL III longitudinal cohort during the defined window, of which 1375 (95.0%) followed up for baseline eye examination. Ebola survivors (635/661, 96.1%) and adult close contacts (727/767, 94.8%) demonstrated a comparable likelihood for presenting for eye examination (odds ratio [OR] 0.68, 95% confidence interval [CI] 0.36-1.28). In an adjusted model, age over 50 (OR 10.2, 95% CI 1.35-77.3) and living outside Montserrado County (OR 0.18, 95% CI 0.10-0.33) were associated with the likelihood of presenting for a baseline comprehensive eye examination. CONCLUSION: Most EVD survivors and their close contacts who enrolled during the study window presented for eye examinations. Older participants and those who lived closer to clinical facilities were most likely to present. Focused strategies accounting for these factors may assist with organizations planning survivor care in the setting of EVD.